KULTUR JARINGAN RUMPUT LAUT (Gracilaria verrucosa) DI MEDIA BERBEDA TERHADAP PERTUMBUHAN THALLUS - satriani, gloria ika; Maidie, Asfie; Handayani, Sri; Suryati, Ema (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2017)
The aims of this experiment are to know the effect of different medium to seaweed (G. verrucosa) cultured in vitro expressed total number of thallus. The experiment was conducted in the Biotechnology Laboratory of Research Institute for Coastal Aquaculture (RICA) Maros, South Sulawesi. The experiment was arranged in Completely Randomized Design (CRD) with 10 replications and 4 treatments of medium, those are: Sterile Sea Water / SSW 25 ppt, Prevasoli ES Medium / PES, Agrodyke / AG, and Conwy / CW. The last analyze was Least Significant Difference (LSD) to know the best medium to support total number of thallus. The result of the experiment shows that the highest total number of thallus was achieved by SWS (3,75). Keywords: Gracilaria verrucosa, tissue culture, thallus, medium